Synthesis and Characterization of Biodegradable Foam from Cassava Pulp and Sugarcane Bagasse Cellulose with PVA Agent - Sani Sani; Erisa Nur Jannah; Damara Ramadhani Maritza (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
The accumulation of food packaging waste, specifically styrofoam, has become a significant environmental pollutant due to its 500-year degradation period and hazardous chemical content. To address this issue, biodegradable foam (biofoam) made from natural polymers such as starch and cellulose offers a sustainable, economical alternative to conventional styrofoam. This research aims to synthesise and characterise biodegradable foam (biofoam) from cassava pulp and cellulose from sugarcane bagasse as an eco-friendly alternative to styrofoam. Biofoam was synthesised using cassava pulp, cellulose, polyvinyl alcohol (PVA), and glycerol, with varying starch-to-cellulose ratios (1:0.2 to 1:1) and mixing times (5 to 30 minutes), followed by thermopressing at 150°C. Characterization included tensile strength, water absorption, biodegradability, FTIR, and SEM testing. Results showed that the 1:1 ratio with 30-minute mixing give the best properties: 10.4575% water absorption, 41% biodegradability in 30 days, and 5.4916 MPa tensile strength. Water absorption and biodegradability met SNI 7188.7:2016 and ASTM D5988 standards. Although the tensile strength (5.4916 MPa) exceeded commercial styrofoam, it did not meet the 29.1600 MPa SNI requirement. FTIR confirmed the presence of hydroxyl, aliphatic, and carbonyl groups. SEM revealed clumping and cavities on the surface due to incomplete homogenization and starch gelatinization. Contribution to Sustainable Development Goals (SDGs):SDG 11: Sustainable Cities and CommunitiesSDG 12: Responsible Consumption and ProductionSDG 15: Life on Land